Dynamic features of human mitochondrial DNA maintenance and transcription - Akbari, Mansour; Nilsen, Hilde Loge; Montaldo, Nicola Pietro (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are the primary sites for cellular energy production and are required for many essential cellular processes. Mitochondrial DNA (mtDNA) is a 16.6 kb circular DNA molecule that encodes only 13 gene products of the approximately 90 different proteins of the respiratory chain complexes and an estimated 1200 mitochondrial proteins. MtDNA is, however, crucial for organismal development, normal function, and survival. MtDNA maintenance requires mitochondrially targeted nuclear DNA repair enzymes, a mtDNA replisome that is unique to mitochondria, and systems that control mitochondrial morphology and quality control. Here, we provide an overview of the current literature on mtDNA repair and transcription machineries and discuss how dynamic functional interactions between the components of these systems regulate mtDNA maintenance and transcription. A profound understanding of the molecular mechanisms that control mtDNA maintenance and transcription is important as loss of mtDNA integrity is implicated in normal process of aging, inflammation, and the etiology and pathogenesis of a number of diseases.